Clinicopathological evaluation of the lesions of oral cavity, oropharynx, larynx and hypopharynx - Mittal, Himanshu Kumar; Sharma, Dev Raj (International Surgery Journal, 2020)
Background: Early detection of malignancy substantially improves the survival in most head and neck cancers. A simpler and reliable screening method is something that is sought after by every clinician. Hence a clinicopathological study was carried out in the local population to study the pattern of various factors associated with the clinically suspicious lesions of the oral cavity, oropharynx, larynx and the hypopharynx. The role of exfoliative cytology was also evaluated. Methods: Our study, comprised of a total of 50 cases clinically suspicious of being either premalignant or malignant lesions of the oral cavity, oropharynx, larynx and the hypopharynx. All the patients were examined thoroughly and diagnosed clinically. Thereafter they were subjected to both exfoliative cytology and histopathology. Results: A malignant laryngeal lesion was the commonest. clinical diagnosis seen in 68% of the cases. On exfoliative cytology, the commonest finding was squamous cell carcinoma, seen in 34 (68%) cases. On histopathological examination, squamous cell carcinoma was found to be the commonest with 39 (78%) cases. The sensitivity and specificity of exfoliative cytology were observed as 84.6% and 90.90% respectively. The methods of diagnosis applied and their results were found to be significantly associated with a p value of 0.0119 which was <0.05. Conclusions: The commonest cause for the suspicious lesions of the oral cavity, oropharynx, larynx and hypopharynx was squamous cell carcinoma seen in 78% of the cases. Rapid assessment tools like exfoliative cytology can aid in early detection of malignant lesions.